Endoscopic imaging results: web-based solution for video diffusion with real-time assistance - Braga, Joel Teles (2014)
The technological evolution seen in the past years led to an increase in the number therapeutic and diagnostic tests. In this paper a new solution for storage, diffusion, and real-time remote assistance in endoscopic exams is presented. The aim is to solve the problem of endoscopic examinations not being archived and easily accessed anywhere within a health care network by authorized health care professionals and researchers. Solving that problem avoids unneeded repetition of unpleasant exams and allows the comparison of video segments with future procedures. The presented solution also allows the streaming and real-time remote assistance of exams being carried out. This way health care professionals can contribute with their expertise even if they cannot attend onsite.